Development of a STREAM-Based Self-Study Module to Stimulate HOTS in Petroleum Study Materials - Hadi, Kuncoro; Mahartika, Ira; Yasthophi, Arif (KnE Social Sciences, 2024)
This study aimed to develop a STREAM-based self-study module to stimulate HOTS in petroleum study materials and to test the effectiveness of the module. This developmental research used the 4D method. This research began with a literature study and observations of class XI MIPA students to see the material used and the learning process, as well as to find out the obstacles to learning. The initial conditions provided ideas for making STREAM-based self-study modules that are expected to stimulate students’ HOTS. The module was tested on a limited basis on online classes of XI MIPA 3 to see its practicality. In completing the module, an expert feasibility test was carried out. The expert test showed that the STREAM-based learning module to stimulate HOTS was in the very appropriate category with an average score of 94.55%. For the very decent quality category with a value of 93.13%, for the learning quality category, it was in the very feasible category with a score of 94, 28%., and 96.25% in the very decent category for technical quality (media). The very feasible category was at 96.67% for student readability. The use of STREAM-based self-study modules to facilitate HOTS was proven to be effective and can be used in the learning process. In modules with the STREAM approach to learning chemistry, students can develop independent learning skills and higher thinking skills. Keywords: STREAM-based self-study, HOTS, petroleum